Accuracy of molecular diagnostics in pemphigus and bullous pemphigoid: comparison of commercial and modified mosaic indirect immunofluorescence tests as well as enzyme-linked immunosorbent assays - Gornowicz-Porowska, Justyna; Seraszek-Jaros, Agnieszka; Bowszyc-Dmochowska, Monika; Kaczmarek, Elżbieta; Pietkiewicz, Paweł; Bartkiewicz, Paweł; Dmochowski, Marian (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Pemphigus and bullous pemphigoid (BP) are identified by autoantibodies (abs) against desmoglein 1, 3 (DSG1/3) and BP180/BP230, respectively. A novel mosaic to indirect immunofluorescence (IIF) using purified BP180 recombinant proteins spotted on slide and transfected cells expressing BP230, DSG1, DSG3 is available. The commercial (IgG detection) and modified (IgG4 detection) mosaic for indirect immunofluorescence (IIFc – IIF commercial, IIFm – IIF modified) and IgG ELISAs were evaluated in pemphigus and bullous pemphigoid (BP) molecular diagnostics. Aim : To compare diagnostic accuracy of commercial (IgG detection) and modified (IgG4 detection) mosaic IIF assay and to examine the diagnostic value of ELISAs in relation to mosaic IIF in routine laboratory diagnostics of pemphigus and BP. Material and methods : Sera from 37 BP and 19 pemphigus patients were studied. Associations between tests were assessed using Fisher’s exact test. Results: There are associations between the positive/negative samples detected by IIFc with desmoglein1 (DSG1)/desmoglein3 (DSG3)/BP230 transfected cells and ELISAs and no association between anti-BP180 IgG detection by IIFc and ELISA. IIFm with DSG1 and DSG3 showed both 100% sensitivity and 100% and 78% specificity, respectively, and 100% and 83% positive predictive value in relation to IIFc. IIFm with BP230 had 87% specificity, 55% sensitivity, whereas IIFm with BP180 had a 100% sensitivity and 13% specificity in relation to IIFc. Conclusions : The IIFc with DSG1/DSG3/BP230 transfected cells, excluding BP180 spots, is an alternative method to ELISA in pemphigus/BP diagnostics. IgG4 antibodies, both pathogenically and diagnostically important, are inconsistently detectable with IIFm.